Migration, the quality of the labour force and economic inequality - Martin Kahanec; Klaus F. Zimmermann (Institute for the Study of Labor (IZA), 2008)
Mobility of workers involves flows of labour, human capital and other production factors and thus contributes to a more efficient allocation of resources. Besides these effects on allocative efficiency, migrant flows affect relative wages and also change the international and national distribution of skills and thereby equality in the receiving society. This paper suggests that skilled immigration promotes economic equality in advanced economies under standard conditions. The context is theoretically explained in a core model and empirically documented using unique data from the WIID database and OECD.
urn:nbn:de:101:1-2008062716
Keywords: D33; 330; Inequality; income distribution; human capital; skill allocation; migration; ethnicity; minority; Gini-coefficient; Qualifikation; Allokation; Einwanderung; Hochqualifizierte Arbeitskräfte; Lohnstruktur; Einkommensverteilung; Internationale Arbeitsmobilität; Humankapital; OECD-Staaten